Mapping immune variation and var gene switching in naive hosts infected with Plasmodium falciparum - Milne, K; Ivens, A; Reid, AJ; Lotkowska, ME; O'Toole, A; Sankaranarayanan, G; Munoz Sandoval, D; Nahrendorf, W; Regnault, C; Edwards, NJ; Silk, SE; Payne, RO; et al. (eLife Sciences Publications, 2021)
Falciparum malaria is clinically heterogeneous and the relative contribution of parasite and host in shaping disease severity remains unclear. We explored the interaction between inflammation and parasite variant surface antigen (VSA) expression, asking whether this relationship underpins the variation observed in controlled human malaria infection (CHMI). We uncovered marked heterogeneity in the host response to blood challenge; some volunteers remained quiescent, others triggered interferon-stimulated inflammation and some showed transcriptional evidence of myeloid cell suppression. Significantly, only inflammatory volunteers experienced hallmark symptoms of malaria. When we tracked temporal changes in parasite VSA expression to ask whether variants associated with severe disease rapidly expand in naive hosts, we found no transcriptional evidence to support this hypothesis. These data indicate that parasite variants that dominate severe malaria do not have an intrinsic growth or survival advantage; instead, they presumably rely upon infection-induced changes in their within-host environment for selection.